HTML5 game development for dummies - Harris, Andrew 1964- (For dummies, 2013)
Harris has written the book he wishes he'd had when he started creating games for his own enjoyment. Whether you're new to programming or a skilled programmer eager to cash in on today's game bonanza, this guide helps you build powerful games that also work on mobile devices -- |c Source other than Library of Congress